Improving the photocatalytic performance of graphene–TiO2 nanocomposites via a combined strategy of decreasing defects of graphene and increasing interfacial contact - Zhang, Yanhui; Zhang, Nan; Tang, Zi-Rong; Xu, Yi-Jun (Physical chemistry chemical physics : PCCP, 2012)
Incessant interest has been shown in the synthesis of graphene (GR)-semiconductor nanocomposites as photocatalysts aiming to utilize the excellent electron conductivity of GR to lengthen the lifetime of photoexcited charge carriers in the semiconductor and, hence, improve the photoactivity. However, research works focused on investigating how to make sufficient use of the unique electron conductivity of GR to design a more efficient GR-semiconductor photocatalyst have been quite lacking. Here, we show a proof-of-concept study on improving the photocatalytic performance of GR-TiO(2) nanocomposites via a combined strategy of decreasing defects of GR and improving the interfacial contact between GR and the semiconductor TiO(2). The GR-TiO(2) nanocomposite fabricated by this approach is able to make more sufficient use of the electron conductivity of GR, by which the lifetime and transfer of photoexcited charge carriers of GR-TiO(2) upon visible light irradiation will be improved more efficiently. This in turn leads to the enhancement of visible-light-driven photoactivity of GR-TiO(2) toward selective transformation of alcohols to corresponding aldehydes using molecular oxygen as a benign oxidant under ambient conditions. It is anticipated that our current work would inform ongoing efforts to exploit the rational design of smart, more efficient GR-semiconductor photocatalysts for conversion of solar to chemical energy by heterogeneous photocatalysis.